ТООL SUPPLY THREAD IN PROCESSING TECHNOLOGY OF HIGHTEMPERATURE AND TITANIUM ALLOYS - R. V. Guseynov; E. K. Agakhanov; M. R. Rustamova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Tap machining of high-temperature strength and titanium materials is considered.